The Problems and Challenges of Modern Publishing and Printing Industry of Ukraine - Korinko, Mykola; Zhelikhovskyi, Gnat (Information & Media, 2020)
In this article the author examines the main problems of the prospects of development and some questions of operation of publishing and printing industry within the frameworks of global digitalization and growth of digital publications. The author pays special attention to the priority of the objects of activity of the publishing and printing complex of Ukraine. The purpose of this work is to determine the possible ways of development of the publishing and printing industry of Ukraine on the basis of state regulation of their activities. The results of this work may be used by public institutions in predicting the effective development of the economy and national legislation to support publishing and printing industry.